A Case of Implant Failure in Partial Wrist Fusion Applying Magnesium-Based Headless Bone Screws - Alice Wichelhaus; Judith Emmerich; Thomas Mittlmeier (Case Reports in Orthopedics)
This article presents a case of implant failure resulting in mechanical instability of a scaphotrapezotrapezoideal arthrodesis using magnesium-based headless bone screws. During revision surgery osteolysis surrounding the screws was observed as well as degraded screw threads already in existence at 6 weeks after implantation. The supposed osseous integration attributed to magnesium-based screws could not be reproduced in this particular case. Thus, it can be reasoned that the use of magnesium-based screws for partial wrist arthrodesis cannot be encouraged, at least not in dual use.